2012
DOI: 10.1002/clen.201200023
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Effects of Shrub Canopy on Throughfall and Phreatic Water Using Water Isotopes, Western China

Abstract: Alpine shrub Quercus aquifolioides was selected to study the effects of shrub canopy on throughfall and phreatic water by analyzing the isotopic time series of precipitation, canopy throughfall and phreatic water and examining correlations among these series in Wolong Nature Reserve, Western China. Based on analysis of precipitation data in 2003, the local meteoric water line during the rainy season was dD ¼ 8.and the primary precipitation moisture in this region originated from the Pacific Ocean in the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…In dual isotope space, several studies have shown that TF, SF, and OP δ w tend to fall along similar local MWLs with slopes near 8, although one study found the TF slope to be well below that of OP . Similar to TF–OP single‐isotope differences, the d differences vary among events and studies .…”
Section: Canopy Processes and Their Isotopic Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…In dual isotope space, several studies have shown that TF, SF, and OP δ w tend to fall along similar local MWLs with slopes near 8, although one study found the TF slope to be well below that of OP . Similar to TF–OP single‐isotope differences, the d differences vary among events and studies .…”
Section: Canopy Processes and Their Isotopic Effectsmentioning
confidence: 97%
“…Correlations between event interception loss and TF–OP δ w differences have been weak despite correlation between interception loss and intensity and amount . Smaller storms tend to have a greater likelihood of TF that is isotopically lighter than OP, just as individual events means are more likely than study means to have TF with lighter δ w than OP (Figure (b)). Inter‐event carryover of intra‐canopy vapor or residual storage has greater effects on TF in small storms too.…”
Section: Canopy Processes and Their Isotopic Effectsmentioning
confidence: 97%
See 3 more Smart Citations